Detection of Toxoplasma Antibodies and TNF-α in Rheumatoid Arthritis Patients Treated with Methotrexate - H. Kuba, Rasha; H. Zghair, Khawla; H. Alosami, Mohammed (Iraqi Journal of Science, 2026)
This study was conducted to evaluate the prevalence rate oftoxoplasmosis among 294 rheumatoid arthritis (RA) patients treated withmethotrexate (MTX), 50 RA patients without treatment and 50 samples ashealthy control. Blood samples were collected and the presence of T.gondiiIgG and IgM antibodies was determined by using Enzyme linkedimmunosorbent assay (ELISA). Tumor necrosis factor alpha (TNF-α) wasalso estimated in serum of all subjects by using ELISA method too. Theseroprevalence of toxoplasmosis IgM and IgG in RA+MTX was60(20.408%), and 98(33.33%), in RA patients 4(8%), and 18(36%) while,it was 2(24%), 6(12%) in healthy group. Tumor necrosis factor alpha(TNF-α) was also estimated in serum of all subjects by using ELISAmethod too. The mean levels of TNF-α in seropositive anti-ToxoplasmaIgM and IgG of RA+MTX patients were 3.781 pg/ml ± 0.571) and (36.98pg/ml ± 0.58), in RA patients (25.404 pg/ml ± 1.748) and (40.12 pg/ml ±1.7) while, they were (5.04 pg/ml ± 0.643) and (10.7 pg/ml ± 1.7) inhealthy group. The results showed significant difference (P<0.05) wasfound between treated and untreated patients.